2015
DOI: 10.1093/toxsci/kfv009
|View full text |Cite
|
Sign up to set email alerts
|

Human Inhalation Exposures to Toluene, Ethylbenzene, and M-Xylene and Physiologically Based Pharmacokinetic Modeling of Exposure Biomarkers in Exhaled Air, Blood, and Urine

Abstract: Urinary biomarkers of exposure are used widely in biomonitoring studies. The commonly used urinary biomarkers for the aromatic solvents toluene (T), ethylbenzene (E), and m-xylene (X) are o-cresol, mandelic acid, and m-methylhippuric acid. The toxicokinetics of these biomarkers following inhalation exposure have yet to be described by physiologically based pharmacokinetic (PBPK) modeling. Five male volunteers were exposed for 6 h in an inhalation chamber to 1/8 or 1/4 of the time-weighted average exposure valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Currently, the urine pH effect on renal clearance and systemic disposition have rarely been considered when using in silico techniques to simulate drug and metabolite disposition. For studies that specifically explore urinary excretion as a function of time, the urinary excretion profiles were mostly simulated using simple first order urinary kinetics (Ortiz et al, 2014;Phillips et al, 2014;Adachi et al, 2015;Marchand et al, 2015;Yang et al, 2015) governed by a fixed observed value such as elimination rate constant. Although these models may have successfully recapitulated the observed data, they cannot be extrapolated to untested or altered scenarios due to their nonmechanistic nature when simulating urinary kinetics.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Currently, the urine pH effect on renal clearance and systemic disposition have rarely been considered when using in silico techniques to simulate drug and metabolite disposition. For studies that specifically explore urinary excretion as a function of time, the urinary excretion profiles were mostly simulated using simple first order urinary kinetics (Ortiz et al, 2014;Phillips et al, 2014;Adachi et al, 2015;Marchand et al, 2015;Yang et al, 2015) governed by a fixed observed value such as elimination rate constant. Although these models may have successfully recapitulated the observed data, they cannot be extrapolated to untested or altered scenarios due to their nonmechanistic nature when simulating urinary kinetics.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Mean urinary volatile organic compound (VOC) concentrations ranged up to 11.83 μg/L for highly exposed loading workers and 2.58 μg/L for office workers (Heibati et al 2018). Biomonitoring after inhalation exposure of mixed BTEX compounds is modelled and is available (Marchand et al 2015). Urinary VOC concentration biomonitoring could be a possible measure to BTEX exposure during balneotherapy.…”
Section: Benzene and Alkylbenzenesmentioning
confidence: 99%
“…Blood Pb levels were also measured to determine the extent of Pb exposure, and these levels may be tracked in populations to identify potential contributing factors, such as smoking status, alcohol intake, red meat consumption, geographical location, and tap-water contents (Bellinger et al 1987;Counter, Buchanan, and Ortega 2015;Lopes et al 2015;Ngueta et al 2016). Trace levels of PAH from environmental exposure to diesel exhaust and markers of exposure to toluene, ethylbenzene, and m-xylene were also determined in blood samples from volunteers in controlled chamber studies (Marchand et al 2015;Pleil et al 2011b;Pleil et al 2010). In addition, volatile organic compounds (VOC) released from blood were analyzed to detect changes in cellular respiration, and this technique may be utilized to detect alcohol content in blood to assess the amount of alcohol consumption (Amann et al 2014;de Lacy Costello et al 2014;Pleil 2016;Pleil et al 2014).…”
Section: Traditional Environmental Exposure Assessmentmentioning
confidence: 99%